Understanding how components fail - Wulpi, Donald J. (ASM International, 2013)
One of the first books new engineers and technicians should read. This new third edition of the perennial best seller preserves the core of the previous editions, focusing on the metallurgical and materials evaluation for failure mode identification. Comprehensive information covering the basic principles and practices are clearly explained.
Keywords: Metals -- Fracture.; elektronické knihy; electronic books